2018
DOI: 10.1111/ijd.14007
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of β‐catenin and CD44 immunoexpression in oral lichen planus and squamous cell carcinoma

Abstract: According to the findings of this study, β-catenin and CD44 can differentiate between behavior of OLP and OSCC, while the precancerous nature of OLP and malignant transformation potential of it are not suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…4 In addition, the results of Zargaran et al's research were acceptable regarding the expression of CD44 marker in lichen planus that are consistent with the results of present research. 17 The results of Neppelberg et al's research showed that CD44 marker expression was acceptable in areas with oral lichen planus in epithelial tissues as well as areas with compact tissue, which is consistent with the results of our research. 18 The findings of Chaiyarit et al's research showed that CD44 is a desirable indicator for the diagnosis of oral lichen planus from other epithelial dysplastic lesions that is consistent with the results of our research.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…4 In addition, the results of Zargaran et al's research were acceptable regarding the expression of CD44 marker in lichen planus that are consistent with the results of present research. 17 The results of Neppelberg et al's research showed that CD44 marker expression was acceptable in areas with oral lichen planus in epithelial tissues as well as areas with compact tissue, which is consistent with the results of our research. 18 The findings of Chaiyarit et al's research showed that CD44 is a desirable indicator for the diagnosis of oral lichen planus from other epithelial dysplastic lesions that is consistent with the results of our research.…”
Section: Discussionsupporting
confidence: 92%
“…E-cadherins make connections in epithelial tissues thus keeping the epithelial cells together. 17 Many epithelial neoplasms, including oral squamous cell carcinoma (OSCC), show the changes in the expression of E-cadherin protein. The possibility of this change in extent causes a defect in the ability of the cells to attach to each other and facilitates separation from the primary tumor and attachment to the substrate components and progression to the surrounding tissues.…”
Section: Resultsmentioning
confidence: 99%
“…As has been observed, the expression of CD44 was significantly lower in OSCC in comparison with oral lichen planus which is a precancerous state of OSCC, indicating that CD44 might trigger the malignant conversion from precancerous state to cancer [105]. In pleomorphic adenoma, knockdown of CD44 not only impaired the malignant behaviors of tumor-initiating cells in vitro, but also suppressed tumorigenesis in xenograft mice [106].…”
Section: Cd44 and Tumor Initiationmentioning
confidence: 51%
“…Oral squamous cell carcinoma is, therefore, an important health problem in the global community (2). Oral squamous cell carcinoma occurs in a multi-step process, from the step-by-step accumulation of genetic mutations, which is morphologically known as a precancerous lesion (3). But, mere microscope-based clini-cal signs cannot determine the progression of a precancerous lesion to malignancy.…”
Section: Introductionmentioning
confidence: 99%